Indigenous Beadwork: Drawing Together Images from Indigenous Literature: An Alternative Epistemology - Lirette, Isabella (Contemporary Kanata: Interdisciplinary Approaches To Canadian Studies, 2025)
During the fall of 2022, I participated in an independent study in Indigenous Literatures at Mount Allison University. An important part of this study was examining different themes and images emphasized in the literature I read. I decided to express the knowledge I had gained through a beadwork project on a faux leather file holder (See image 1). Beading has been a way for me to feel more connected to my Indigeneity, and I am very honoured to be able to wear my beads and practice the art of beadwork as a Mi’kmaw woman. This artistic piece brings together some important themes and images from four Indigenous-authored texts: Cherie Dimaline’s The Marrow Thieves, Alicia Elliot’s A Mind Spread Out on the Ground, Thompson Highways, Kiss of the Fur Queen, and Thomas King’s The Truth about Stories: A Native Narrative. Together, these images tie together themes of Indigenous pride, love, resilience, community, and respect. The connectivity between the multiple books is reinforced by bringing these images together.